THE IMPLEMENTATION OF USING QUIZIZZ AND G-FORM DURING THE COVID-19 PANDEMIC BASED ON STUDENTS’ ATTITUDE - Santoso, Hajar Ahmad; Istiqomah, Nisa Rachmi (MaPan : Jurnal Matematika dan Pembelajaran, 2021)
This study aims to evaluate the effectiveness of Quizizz and G-Form media based on students' attitudes in learning mathematics. This study used an experimental method with a two-way analysis of variance (ANOVA) technique and Tukey's test. The population is SMAN 3 Sidoarjo grade XI aged 15-17 years as many as 130 students, while the sample is 64 students. Data collection was carried out using test and questionnaire techniques. The results showed that: (a) the mathematics learning outcomes of students who used the G-Form media were higher than those taught using the Quizizz media, (b) there is an interaction between learning media and learning attitudes towards students' mathematics learning outcomes, (c) for students who have positive learning attitudes, there is no significant difference in mathematics learning outcomes of students using G-Form and Quizizz media, and (d) for students who have negative learning attitudes, there are differences in the mathematics learning outcomes of students taught by the G-Form and Quizizz media. We suggest exploring deeper into this media using material that is more authentic to students.